If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3(x + -6) = 2 Reorder the terms: 5x + -3(-6 + x) = 2 5x + (-6 * -3 + x * -3) = 2 5x + (18 + -3x) = 2 Reorder the terms: 18 + 5x + -3x = 2 Combine like terms: 5x + -3x = 2x 18 + 2x = 2 Solving 18 + 2x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 2x = 2 + -18 Combine like terms: 18 + -18 = 0 0 + 2x = 2 + -18 2x = 2 + -18 Combine like terms: 2 + -18 = -16 2x = -16 Divide each side by '2'. x = -8 Simplifying x = -8
| gh+f=k | | 8/7x+1/3=7/12 | | 10x^2-3x-36=0 | | 8/15=x/12 | | 2/3(12x-6)=-28 | | 5x-3(z-6)=2 | | x*2+4x=-1 | | 26=6x-21 | | 2/15=x/12 | | -36-4x=32 | | 6x+10=3x+6 | | 1/3(6x-3)=-28 | | 9x^2+13x-90=0 | | 16y-9y+12=33 | | (m^2-13-14m^3)+(-2m+10m^2-14m)= | | 68=x+47 | | x-(x-48)=180 | | 10x^2=-55x-60 | | -x/19=5 | | 2x+3x-6=5x-3 | | 3(2-4x)+6=9 | | -5x-29=-49 | | -24-52= | | 8/20=6/15 | | 8/206/15 | | 13(4)= | | 8/2010/4 | | 6x^2-10x+3x-5=0 | | 7.4e+2.6e-9=2e | | 8/20x/2.5 | | 2x-11=-15 | | -24-13(4)= |